Special events : a new generation and the next frontier - Goldblatt, Joe (Hoboken, New Jersey : Wiley, 2011)
"This book chronicles and champions the development, changes, and challenges faced by the global celebrations industry for event planners. New interviews are included with experienced event leaders to give a better understanding of the field. New chapters are included on green events, corporate social responsibility, and theoretical case studies. Event measurement, evaluation, and assessment topics are integrated throughout a number of the chapters. Over 200 new Web resources and appendices show how to save money, time, and improve the overall quality of an event. Event planners will also learn how technology may be harnessed to help them improve their events' financial, quality, environmental and other strategic outcomes."--Provided by publisher."This book chronicles and champions the development, changes, and challenges faced by the global celebrations industry for event planners"--Provided by publisher.
pt. I: Theory of Event Leadership -- 1. Welcome to Planned Events -- 2. Models of Global Planned Events -- -- pt. II: Event Administration -- 3. Developing and Implementing the Event Plan -- 4. Event Leadership Through Human Resource and Time Management -- 5. Financial Administration -- 6. Greener Events -- -- pt. III: Event Coordination -- 7. Managing Vendor Contracts -- 8. On-Site Event Production -- -- Pt IV: Event Marketing -- 9. Advertising, Public Relations, Promotions, and Sponsorships -- 10. Online Marketing and Consumer-Generated Media -- -- pt. V: Legal, Ethical, and Risk Management -- 11. Risk Management: Legal and Financial Safeguards -- 12. Inclusiveness, Morality, Law, and Ethics in Event Planning -- 13. Doing the Right Thing: Corporate Social Responsibility (CSR) -- -- pt. VI: Technology for Professional Development -- 14. Technology and Modern Event Planning -- 15. Career Development, Advancement, and Sustainable Success -- 16. The New Best Practices in Planned Events -- 17. New Frontiers in Twenty-First-Century Planned Events.
Includes bibliographical references and index.
Keywords: SPECIAL EVENTS MANAGEMENT